What kind of baby-sitter is this? - Johnson, Dolores, 1949- (New York : Macmillan Pub. Co.; Toronto : Collier Macmilllan Canada ; New York : Maxwell Macmillan International Pub. Group, 1991)
Kevin intensely dislikes the idea of having a babysitter, until the unconventional baseball-loving "Aunt" Lovey arrives to change his mind.
Keywords: Babysitters -- Fiction; African Americans -- Fiction